2019
DOI: 10.1063/1.5084730
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cernox thermometers in AC specific heat measurements under pressure

Abstract: We report on the resistance behavior of bare-chip Cernox thermometers under pressures up to 2 GPa, generated in a piston-cylinder pressure cell. Our results clearly show that Cernox thermometers, frequently used in low-temperature experiments due to their high sensitivity, remain highly sensitive even under applied pressure. We show that these thermometers are therefore ideally suited for measurements of heat capacity under pressure utilizing an ac oscillation technique up to at least 150 K. Our Cernox-based s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Details of the setup and the measurement protocol are described in Ref. 25. A hybrid piston-pressure cell, made out of Grade 5 titanium alloy (Ti 6Al-4V; outer cell body) and Ni-Cr-Al alloy (inner cell body) 26 , was used to apply pressure up to 2.08 GPa.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the setup and the measurement protocol are described in Ref. 25. A hybrid piston-pressure cell, made out of Grade 5 titanium alloy (Ti 6Al-4V; outer cell body) and Ni-Cr-Al alloy (inner cell body) 26 , was used to apply pressure up to 2.08 GPa.…”
Section: Methodsmentioning
confidence: 99%
“…In our efforts to determine the phase diagram of iron-based superconductors under hydrostatic pressure, which typically undergo a cascade of phase transitions over wide temperature ranges, we recently reported on an optimization of the thermometry of such an ac calorimetry setup to measure specific heat over wide temperature ranges in conventional piston-pressure cells up to 2.5 GPa ( Figure 2). [103] By utilizing commercially available Cernox thermometers to pick up the temperature oscillations of the sample, we demonstrated that we can measure the specific heat of a sample of interest over a temperature range as wide as up to 150 K (and likely even larger). In Sections 3 and 4, we will show how our combined efforts of transport and thermodynamic investigations under hydrostatic pressure (in particular those of the specific heat, using the aforementioned optimized ac calorimetric technique) have advanced the understanding of the phase diagrams of several iron-based superconductors.…”
Section: Measurement Probes Under Hydrostatic Pressurementioning
confidence: 98%
“…Uniaxial pressure is distinct from hydrostatic pressure, as the applied force, which acts on the crystal, is highly directional. [103] Copyright 2019, AIP Publishing.…”
Section: Uniaxial Stress and Strain Control In Piezo-based Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific heat measurements under pressure were performed using an ac calorimetry technique on a third sample (sample S3) in a cryogen-free cryostat from ICEOxford (Lemon-Dry) with base temperature of 1.4 K. Details of the setup used and the measurement protocol are described in Ref. 23.…”
Section: Methodsmentioning
confidence: 99%